Development Study: Ethnomathematics-Based Digital Worksheets With A Realistic Approach - Saputri, Winda Alma; Wahyuni, Sri (Universitas Wiralodra, 2024)
Cultural diversity in Indonesia can be utilized by integrating it into education using a learning model, the RME or PMR. The developmenti of technology in the latest era shapes new mindsets and attitudes in society, requiring discoveries in mathematics learning. This study aims to create an interactive learning medium based on digital technology for junior high school students in grade VIII.B that is valid, practical, effective, and has a potential effect on student learning outcomes. The type of research applied is design research type development study and consists of two stages, namely preliminary and formative evaluation (self-evaluation, expert reviews, one-to-one, small group, and field test). The data analysis method is carried out descriptively using questionnaire results, interview results, and student tests. Based on what will happen, the media research developed must be valid, practical, effective, and have a potential impact. The validity is seen from the validation of material experts as much as 3.4 and media experts as much as 3.28, which is included in the very valid category. Furthermore, the media can be used by students to determine the practicality of the LKPD digital media. The practicality of learning media that has been developed in the small group step of 3.4 is included in the very easy or very practical category. Students are given a test before and after using the LKPD Digital media to determine the effectiveness of LKPD Digital. It was found from the N-Gain Score test results that the LKPD digital media was quite effective.